FACTORS ASSOCIATED WITH ANTIHYPERTENSIVE MONOTHERAPY AMONG US ADULTS WITH TREATED AND UNCONTROLLED BLOOD PRESSURE, NHANES 2005-2016. (April 2021) - Derington, Catherine; King, Jordan; Herrick, Jennifer; Dixon, Dave; Cohen, Jordana; Shimbo, Daichi; Kronish, Ian; Saseen, Joseph; Muntner, Paul; Moran, Andrew; Bress, Adam
Abstract: Objective: Combining antihypertensive medication classes more efficaciously lowers blood pressure (BP) than monotherapy. We sought to determine factors associated with antihypertensive monotherapy in US adults with uncontrolled BP. Design and method: This serial, cross-sectional study analyzed pooled data from the 2005–2008, 2009–2012, and 2013–2016 US National Health and Nutrition Examination Survey (NHANES) cycles. We included NHANES participants age 20 years or older with hypertension taking antihypertensive medication and with uncontrolled BP, defined as systolic BP of 140 mm Hg or greater or diastolic BP of 90 mm Hg or greater (N = 2, 699). Antihypertensive medication use was obtained from a medication inventory of participants' pill bottles. We calculated prevalence ratios (PRs) and 95% confidence intervals (CIs) for antihypertensive monotherapy versus taking more than one antihypertensive medication associated with each characteristic using multivariable adjusted Poisson regression models with robust standard errors. Results: The proportion of US adults with hypertension and uncontrolled BP taking monotherapy was 35.7%, 36.3%, and 37.9% in 2005–2008, 2009–2012, and 2013–2016, respectively. After multivariable-adjustment, monotherapy was more common among current smokers (PR 1.26, 95%CI 1.06–1.50) compared to never/former smokers. Monotherapy was less common among participants 75 years or older (PR 0.71, 95%CI 0.53–0.95) compared to participants younger than 40 years, females (PR 0.81, 95%CI 0.71–0.92) compared to males, non-Hispanic black adults (PR 0.76, 95%CI 0.65–0.89) compared to non-Hispanic white adults, and obese (PR 0.73, 95%CI 0.63–0.86) compared to normal/underweight participants. Monotherapy was also less common among participants with versus without diabetes (PR 0.80 95%CI 0.67–0.94), coronary heart disease (PR 0.73, 95%CI 0.54–0.98), chronic kidney disease (PR 0.80, 95%CI 0.68–0.94), and heart failure (PR 0.46, 95%CI 0.29–0.73). Conclusions: Among US adults with hypertension and uncontrolled BP, smoking was positively associated with monotherapy use while older age, female sex, and comorbidities of diabetes, coronary heart disease, chronic kidney disease, and heart failure were associated with a lower prevalence of monotherapy use. The extent to which other factors such as clinician or patient preferences, adverse medication effects, or therapeutic inertia influence monotherapy among those with uncontrolled BP need to be investigated.